Derajat Gangguan Dengar dan Letak Perforasi Membran Timpani pada Pasien OMSK : Sebuah Seri Kasus - Aditomo, Rano; Swasti Wijayanti, Renny; Selvi Yanuarista, Gabrina (Majalah Kedokteran Indonesia, 2024)
Introduction: Chronic suppurative otitis media (CSOM) is an inflammation of the middle ear characterized by a perforation of the tympanic membrane with mucoid or mucopurulent secretions that persists or intermittently for 8 weeks. Tympanic membrane perforation causes a decrease in the surface area of ​​the tympanic membrane for sound transmission and causes sound waves to be directly transmitted to the middle ear. CSOM may cause hearing loss from mild to deafness. Case reports: This research is a case series was conducted at the ENT Department in Sultan Agung Islamic Hospital Semarang during September 2022-January 2023. A total of 7 patients were admitted to the ENT Department in Sultan Agung Isalmic Hospital with diagnosis of CSOM. 6 patients (86%) had hearing loss and 1 patient (14%) had only tinnitus without any hearing loss. As many as 67% had CHL and 19% had MHL and SNHL. The most common perforations were found in the AI ​​quadrant (43%) followed by the AS and PI quadrants (28.5% each). Patients with perforation experienced the heaviest degree of hearing loss in the AS quadrant (82.5db) and the mildest in the AI ​​quadrant (32.5db). Conclusion: Patients with perforations in the PI quadrant have a worse degree of hearing loss than those with perforations in the AI ​​quadrant, especially in cases of Conductive Hearing Loss. Patients with a larger perforation area have a worse degree of hearing loss than those with smaller area of perforation.